ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP PRAKTIK MANAJEMEN LABA (Studi pada Perusahaan Manufaktur di Indonesia) - Rafdan Anggana, Gea; Prastiwi, Andri (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to analyze the impact of corporate governance mechanism towards earning management. The independent variables in this research, which represent the corporate governance mechanism are independent commissionaire, audit committee, external auditor quality and also managerial ownersip with control variables including leverage and company size. Earning management, as the dependent variable, in this research is measured by discretionary accrual as the proxy of earning management. Data used in this research is annual report and audited financial report from each company, published through website www.idx.co.id The sample used in this research are manufacturing companies listed in Indonesian Stock Exchange during 2008 up to 2011. The data collection method used in this research is purposive sampling, resulted 140 obseravtions during four years from 35 companies. This research conclude that independent commissionaire, external auditor quality and managerial ownership have the significant and negative impact towards earning management. On the other contrary, audit committee doesn’t significantly influence earning management. Generally, from this research, good corporate governance mechanisms significantly affect the earning management.